2019
DOI: 10.1177/1758573218825392
|View full text |Cite
|
Sign up to set email alerts
|

The role of structured physiotherapy in treating patients with atraumatic shoulder instability: Medium term results from a case series

Abstract: Background Consensus favours conservative treatment for atraumatic shoulder instability, but literature is scarce on the topic. We therefore prospectively assessed the results of structured physiotherapy for these patients. Methods Patient reported outcomes were recorded prior to physiotherapy and on discharge. Notes review identified patients re-referred for the same condition. Results N = 85. Review range was 12–72 months post-treatment. Median Oxford Shoulder Instability Score (OSIS) improved from 21 (range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 34 publications
(41 reference statements)
0
25
0
Order By: Relevance
“…The number of participants receiving physiotherapy was approximately 491 ranging from 15 [27] to 85 [16]; one study reported the number of shoulders rather than participants [28]. The mean age of participants was similar between studies, ranging from 16 [29] to 25 years [28].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of participants receiving physiotherapy was approximately 491 ranging from 15 [27] to 85 [16]; one study reported the number of shoulders rather than participants [28]. The mean age of participants was similar between studies, ranging from 16 [29] to 25 years [28].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…One provided an age and gender-adjusted Constant score [28]. The other adjusted for several confounding factors [16].…”
Section: Confounding Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the wider research available on shoulder pain, there is emerging evidence in support of tailoring education to the patient, with activity and general exercise promotion, for example, recommended in patients who have a sedentary lifestyle [54]. Education is advocated in managing ASI following a recent case series involving 85 patients [55] and also features in the BESS guidelines [17]. Given the high utilisation of education, there is justification for further research to investigate this aspect of management and inform future practice.…”
Section: Education and Advicementioning
confidence: 99%
“…Poor prognoses for patients may plausibly be due to delayed and/or inaccurate diagnoses, and inappropriate treatment selection (15). There are many models available for the diagnosis (3,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) and management (15,16,(29)(30)(31)(32)(33) of shoulder instability, but clinical practice is not routinely drawing on these models. Existing models and guidelines recognise that the underpinning evidence base used to inform clinical decision making is limited and heavily informed by expert opinion (24,32,34).…”
Section: Introductionmentioning
confidence: 99%